Impact of Percutaneous Revascularization on Left Ventricular Mass and Its Relationship to Outcome in Hypertensive Patients With Renal Artery Stenosis. (12th March 2020) - Iwashima, Yoshio; Fukuda, Tetsuya; Horio, Takeshi; Kusunoki, Hiroshi; Hayashi, Shin-ichiro; Kamide, Kei; Kawano, Yuhei; Ishimitsu, Toshihiko; Yoshihara, Fumiki
Abstract: BACKGROUND: We investigated the effects of percutaneous transluminal renal angioplasty on left ventricular (LV) mass, and the impact of LV mass reduction on outcomes. METHODS: A total of 144 hypertensive patients with renal artery stenosis (RAS) (mean age 69 years; 22.2% fibromuscular dysplasia (FMD)) who underwent angioplasty were included. Echocardiography was performed at baseline and after 1 year, and patients were thereafter followed up for a median of 5.6 years for primary composite outcomes. RESULTS: In both the FMD and atherosclerotic stenosis (ARAS) groups, LV mass decreased after angioplasty, but the decrease in LV mass index (−15.4 ± 18.3% vs. −0.8 ± 27.8%, P < 0.01) as well as the regression rate of LV hypertrophy was greater in FMD. Multiple logistic regression analysis indicated that FMD (odds ratio (OR) 2.94, P < 0.01), severe RAS (≥90%) (OR 2.94, P < 0.05), and higher LV mass index at baseline (OR 2.94 for 1 SD increase, P < 0.001) were independent predictors of LV mass index decrease of at least 20%. The primary composite outcomes occurred in 45 patients (31.3%). In FMD, lower LV mass index after 1 year (hazard ratio 2.81 for 1 SD increase, P < 0.05) or regression of LV mass (hazard ratio 0.75 for 5% decrease, P = 0.054) showed a tendency to be associated with better outcomes; however, these associations were not found in ARAS. CONCLUSIONS: Hypertensive patients with ARAS have less regression of LV mass in response to angioplasty than those with FMD, and LV mass regression is less useful as a surrogate marker of outcomes especially in ARAS.